Penyuluhan Tentang Pengolahan Sampah Terpadu Menuju Zero Waste Di Kelurahan Karang Pule Kecamatan Sekarbela Kota Mataram - Ratna Yuniarti; Hasyim Hasyim; IAO Suwati Sideman; Desi Widianty; Syamsul Hidayat (Universitas Mataram, 2023)
As a result of increasing population, the quantity of solid waste is continuing to grow. The most common method for the disposal of solid waste is landfilling. However, huge negative environmental impacts such as odor, dust, contamination of groundwater are among the problems that arise due to disposal of solid waste in landfill sites. Therefore, reduction of solid waste going to landfill is important issue to implemented. Achievement of this target depends upon active waste minimization being practices by all part of the community. This community service program was conducted in Karang Pule, Sekarbela district, Mataram. The aims of the activity were to provide knowledge and increasing public awareness regarding to the urgency of reducing the amount of waste sent to landfill sites, utilizing waste as much as possible through reduce, reuse, recycling (3R) in accordance with the principles of waste management hierarchy towards zero waste. In addition, the process of utilizing organic waste into compost for plant fertilizers was demonstrated. The community service program was also carried out by involving the participants on composting process. The results of the evaluation showed that the participants were very interested and understood the material provided.